National Law in the Shadow of International: Is the Constitution Still Sovereign? (RechtJiva, 2025)
The objective of this research is to analyze the impact of decisions made by international organizations on changes in domestic policies, including at the constitutional level, and to explore how countries manage the balance between international obligations and their constitutional sovereignty. This study also aims to compare two primary approaches to the application of international law within domestic legal systems, namely monism and dualism, and to identify the implications of each approach on state sovereignty. This research employs a qualitative approach with a normative-analytical method. The data used include primary legal sources, such as national constitutions, international treaties, and decisions from international institutions such as the WTO, the International Court of Justice, and the United Nations. Additionally, this study examines literature related to theories of international and domestic law to understand how international obligations influence domestic legal policies. A comparative analysis is used to identify the differences between monism and dualism in the implementation of international law across various countries. The research finds that decisions made by international organizations, such as the WTO and the International Court of Justice, have a significant impact on domestic policies, even at the constitutional level. Countries that adopt a monist system tend to implement international obligations more easily, but are at risk of violating fundamental constitutional principles. On the other hand, countries that adopt dualism are more selective in implementing international obligations through the legislative process, although this can slow down implementation. Countries must strike a balance between fulfilling international obligations and preserving their constitutional sovereignty, depending on the legal approach they adopt.